Laser-induced fluorescence of PO photofragments of organophosphates - Bobrovnikov, Sergei M.; Gorlov, Evgeny V.; Zharkov, Viktor I.; Safyanov, A. D. (Atmospheric and oceanic optics)
The spectrum of phosphorus monoxide (PO) fluorescence is calculated. It is shown that the use of excitation radiation at wavelengths near the bandheads of the (P22 + Q12) and P12 branches of the A2Σ+ (v′ = 0) − X2Π3/2 (v′′ = 0) band provides a spectral separation of the γ (0, 1) PO fluorescence band and the vibrational–rotational Raman spectrum of oxygen. The spectra of the γ (0, 1) fluorescence band of PO fragments of dimethylmethylphosphonate and the vibrational-rotational band of spontaneous Raman scattering on atmospheric oxygen molecules are experimentally obtained under exposure to KrF-laser radiation at a wavelength of 247.78 nm. It is shown that the shape and position of the fluorescence spectra calculated agree well with the experimental data.